2011
DOI: 10.4061/2011/263585
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Stiffness and Increased Pulse Pressure in the Aging Cardiovascular System

Abstract: Aging leads to a multitude of changes in the cardiovascular system, including systolic hypertension, increased central vascular stiffness, and increased pulse pressure. In this paper we will review the effects of age-associated increased vascular stiffness on systolic blood pressure, pulse pressure, augmentation index, and cardiac workload. Additionally we will describe pulse wave velocity as a method to measure vascular stiffness and review the impact of increased vascular stiffness as an index of vascular he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(128 citation statements)
references
References 76 publications
4
115
0
9
Order By: Relevance
“…Our new observation that ABCA1-dependent serum CEC is the fi rst strong parameter that follows those well known to be predictive of PWV (age, blood pressure, and BMI) ( 38,39 ) is consistent with the idea that functionally conserved HDL, infl uencing cholesterol traffi cking in the arterial wall, may contribute to limit vessel stiffness. A very recent work showed that arterial stiffness, evaluated as PWV, correlates with circulating oxidized LDL in healthy subjects, pointing to the importance of lipid metabolism on this parameter ( 40 ).…”
Section: Discussionsupporting
confidence: 66%
“…Our new observation that ABCA1-dependent serum CEC is the fi rst strong parameter that follows those well known to be predictive of PWV (age, blood pressure, and BMI) ( 38,39 ) is consistent with the idea that functionally conserved HDL, infl uencing cholesterol traffi cking in the arterial wall, may contribute to limit vessel stiffness. A very recent work showed that arterial stiffness, evaluated as PWV, correlates with circulating oxidized LDL in healthy subjects, pointing to the importance of lipid metabolism on this parameter ( 40 ).…”
Section: Discussionsupporting
confidence: 66%
“…The increase of pulse pressure (the pulsatile component of blood pressure) is an age-related phenomenon and the common belief is that it is an indicator of large artery stiffness [18] and an established marker of cardiovascular risk in different clinical settings [19,20]. High pulse pressure may derive both from a rise in systolic values and from a decrease in diastolic values.…”
Section: Discussionmentioning
confidence: 99%
“…Complementando, Steppan et al (2011) descrevem que a espessura da íntima-média em humanos triplica entre os 20 e os 90 anos de idade. Para Collins et al (2014) o aumento da espessura aórtica ocorre com predomínio do incremento intimal, enquanto a túnica média permanece praticamente constante com a idade.…”
Section: Resultsunclassified